2020
DOI: 10.3390/nu12030683
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intestinal Microbiota and Predicted Metabolic Pathways During Colonic Fermentation of Mango (Mangifera indica L.)—Based Bar Indigestible Fraction

Abstract: Mango (Mangifera indica L.) peel and pulp are a source of dietary fiber (DF) and phenolic compounds (PCs) that constituent part of the indigestible fraction (IF). This fraction reaches the colon and acts as a carbon and energy source for intestinal microbiota. The effect of mango IF on intestinal microbiota during colonic fermentation is unknown. In this study, the isolated IF of a novel 'Ataulfo' mango-based bar (snack) UV-C irradiated and non-irradiated (UVMangoB and MangoB) were fermented. Colonic fermentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 63 publications
1
14
0
1
Order By: Relevance
“…Ataulfo) peel, as the levels of Bifidobacterium , Lactobacillus , Dorea , and Lactococcus were increased after 72 h of in vitro colonic fermentation. In a later study, Gutierrez-Sarmiento et al [ 48 ], analyzed the effects of the indigestible fraction from a mango-based bar (Ataulfo var.) on the gut microbiota composition through an in vitro gut fermentation model.…”
Section: Interactions Between Mango Polyphenols and The Intestinal Microbiotamentioning
confidence: 99%
“…Ataulfo) peel, as the levels of Bifidobacterium , Lactobacillus , Dorea , and Lactococcus were increased after 72 h of in vitro colonic fermentation. In a later study, Gutierrez-Sarmiento et al [ 48 ], analyzed the effects of the indigestible fraction from a mango-based bar (Ataulfo var.) on the gut microbiota composition through an in vitro gut fermentation model.…”
Section: Interactions Between Mango Polyphenols and The Intestinal Microbiotamentioning
confidence: 99%
“…The health-promoting effects of galloylated compounds are often attributed to their antioxidant activity, although they exert numerous biological activities. Galloylated compounds are not only alternative sources of gallic acid under gastrointestinal conditions [42], but are also potent metabolic enzyme inhibitors [43][44][45] and prebiotic substances [46]. A number of in vitro and in vivo studies has previously shown that pentagalloylglucose exhibits a wide range of biological activities, such as anti-inflammatory, anti-angiogenic, antitumor, and antibacterial activity, and a broad range of antiviral activities [47] that make Fr5 suitable for a possible exploitation for biological and pharmacological studies.…”
Section: Hplc/esi-ms/ms and 1 H Nmr Analysis Of Fr1-fr6 Fractionsmentioning
confidence: 99%
“…Flavonoids could further change the composition of gut microbiota by increasing the growth of Bifidobacteria and Lactobacilli [ 291 ], especially by fermentation procedures of fruit or vegetables rich in antioxidant plant compounds, e.g., fermented papaya was shown to reduce oxidative stress in AD patients, thereby probably reducing neuronal damage [ 292 ]. Furthermore, mango was shown to positively affect intestinal microbiota by increasing the presence of Faecalibacterium , Bifidobacterium , Prevotella and Bacteriodes which are beneficial for human gut health [ 293 ]. A recent study further demonstrated that pomegranate stimulated the growth of Akkermansia munciniphila, which plays an important role in the breakdown of phenolic intestinal compounds and may thereby contribute to its prebiotic effects [ 294 ].…”
Section: Therapeutic Options/perspectives To Slow Down Cognitive mentioning
confidence: 99%